Improving Indonesian Language Learning Outcomes through the Demonstration Method among Eighth-Grade Students at SMPN Batu, Polewali Mandar Regency - Basri, Subianto; Jahara, Jahara (Austronesian: Journal of Language Science & Literature, 2025)
The research objectives of this study were all 44 eighth-grade students of SMPN Batu, Polewali Mandar Regency. The research was conducted in two cycles, with the following processes: (a) planning actions, (b) implementing actions in cycles I and II, (c) conducting research/observations during cycles I and II, (d) conducting a final evaluation of the cycle, (e) analyzing data from evaluation and observation results, (f) conducting reflection based on the analysis and student responses. The results of the study showed the following: (1) the average score obtained by students on the final test of cycle I was 74.89, and the average score on the final test of cycle II was 82.39. (2) student learning outcomes improved in each cycle. This can be seen from the data showing that the comparison of the percentage of learning completion and learning failure in cycle I was 90.9:9.1, while in cycle II it was 100:0. (3) learning using the demonstration method is very effective in improving the learning outcomes of Indonesian language students in grade VIII of SMPN Batu, Polewali Mandar Regency. From the results of this study, it was concluded that by implementing the demonstration teaching method at SMPN Batu, Polewali Mandar Regency, grade VIII, learning outcomes in the Indonesian language subject can be improved.